GENNOVATE: Enabling gender equality in agricultural and environmental innovation - Study concepts and methodology - Elias, Marlène; Rietveld, Anne M. (Bioversity International, 2018)
This presentation was given during a webinar hosted by CGIAR Collaborative Platform for Gender Research on July 12, 2018. Marlene Elias and Anne Rietveld of Bioversity International gave the presentation.